Analisis Normatif Status Kepemilikan Apartemen/Rumah Susun Dalam Perspektif Hukum Agraria Di Indonesia - Riviyusnita, Rianda; Husnaini, Husnaini; Chandra, Andi (Lex Librum : Jurnal Ilmu Hukum, 2025)
Ownership of apartments or flats in Indonesia can be obtained through Freehold Title, Right to Build (HGB) and Other Management Rights (HPL). Apartment ownership in Indonesia adheres to the principle of vertical attachment, which stipulates that objects, buildings and anything above or below a plot of land are considered one entity with the land itself. Although SHM ownership of flats is individual, it cannot be understood that SHM ownership of flats is proof of absolute ownership of land in general. Thus, the legality of SHM ownership of flats (apartment units) is attached to land rights. This results in SHM ownership of flats attached to HGB and Other Management Rights ending or becoming invalid when the term of the HGB and Other Management Rights has expired.